Tanmiyatu Al-Mahârat Al-Lughawiyyah Fî Madrasati Al-Mutawasitati Wa Markaz Al-Tahfidz Minhajul Haq Purwakarta - Ibrahim, Rosmala; Abas, Zainul; Qosim, Muh Nanang (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2023)
إن تعليم اللغة العربية هو إيصال المعلم على اللغة العربية ومعرفتها إلى أذهان التلاميذ بطريقة قويمة لكي يحصلوا على المهارات اللغوية الأربع المنشودة، وهي مهارة الاستماع، الكلام، القراءة والكتابة. هذه الفنون الأربعة لها دور كبير في تعليم اللغة العربية فعلى ذلك يطلب من تعليم اللغة العربية طرق لتنيمة هذه المهارات الأربع لترقية قدرة الطلبة في استخدام اللغة العربية لا سيما لغير الناطقين بها. وينبغي لمعلمي اللغة العربية المحاولات في تنميتها ليحصل عليهم غياة تعليم اللغة العربية وتحقيق ذلك القيام بها في المدارس. فيستهدف هذا البحث لتحليل تنمية مهارة اللغوية في تعليم اللغة العربية في مدرسة المتوسطة ومركز التحفيظ منهاج الحق وكشف الفروق والمساواة في تنميتها بينهما. وتسلك هذه الدراسة منهج الوصفي بدراسة المقارنة. ويتم جمع البيانات عن طريق الملاحظة والمقابلات والوثائق المتعلقة بعنوان البحث. أثبتت الدراسة من خلال نتائجها على وجود المحاولات في تنمية المهارات اللغوية في مدرسة المتوسطة ومركز التحفيظ منهاج الحق وتسير محاولتها داخل الفصل كان أم خراجه. واكتشف من خلال التحليل المساواة والفروق فيها بينهما Teaching the Arabic language is the teacher’s introduction of the Arabic language and its knowledge to the minds of the students in a correct way so that they obtain the four desired linguistic skills, which are the skills of listening, speaking, reading and writing. These four arts have a major role in teaching the Arabic language. Therefore, teaching the Arabic language requires ways to develop these four skills to improve students’ ability to use the Arabic language, especially for non-native speakers. Arabic language teachers should try to develop it to achieve the goal of teaching the Arabic language and achieving this in schools. This research aims to analyze the development of linguistic skill in teaching the Arabic language in middle school and the Minhaj al-Haq memorization center and to reveal the differences and equality in its development between them. This study follows a descriptive and comparative approach. Data is collected through observation, interviews, and documents related to the research topic. The study demonstrated, through its results, the existence of attempts to develop language skills in the middle school and the Minhaj al-Haq Memorization Center and the progress of its attempts, whether inside or outside the classroom. Through analysis, he discovered equality and differences between them.